PENGARUH BALANCE EXERCISE TERHADAP RISIKO JATUH PADA LANSIA DI WILAYAH PUSKESMAS DELI TUA KABUPATEN DELI SERDANG - zuliawati, zuliawati; Hariati, Hariati (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Aging is a process of tissue degeneration in which body function decreases, causing postural balance disorders, which can result in an increased risk of falls in the elderly. Postural balance disorders can be controlled with non-pharmacological therapy, namely balance exercise. This research aims to determine the effect of balance exercise on the level of postural balance in reducing the risk of falls in the elderly. This research uses quantitative research data with the Quasy Experiment method. The number of samples was 31 respondents. The sampling technique uses purposive sampling. Statistical tests use the Pairet Sample test. The results of the study showed that there was a difference in the risk of falls in the elderly before and after doing balance training. The results of the paired sample test obtained pvalue: 0.000 < 0.05 so it can be concluded that there is an influence between balance training and the risk of falls in the elderly. The benefits of balance training are that it helps increase muscle strength in the lower extremities (legs) and improves the vestibular system/body balance.